FORMULASI SEDIAAN MASKER ANTIOKSIDAN DARI EKSTRAK TEH HIJAU (CAMELLIA SINENSIS) - desi nawangsari (Universitas Harapan Bangsa Purwokerto, 2018)
Abstract Research has been carried out on the formulation of maskantioxidant preparations containing green tea leaf extract. The study begins with testing the antioxidant activity of ethanol extract of green tea leaves with a free radical reduction method of 1,1-diphenyl-2-picrylhydrazyl using visible spectrophotometry. Testing of antioxidant activity showed that the ethanol extract of green tea leaves gave an IC50 value of 3.17µg / mL. Formulations of gel masks made were F0 (base without active substances), F1 (base + concentration of ethanol extract of green tea leaves for IC50 (0,000317%)), F2 (base + concentration of ethanol extract of green tea leaves for 50xIC50 (0, 0158%)), F3 (base + concentration of ethanol extract of green tea leaves for 100xIC50 (0.0317%)), F4 (base + concentration of ethanol extract of green tea leaves for IC50), F5 (base + concentration of ethanol extract of green tea leaves worth IC50), F6 (base + concentration of ethanol extract of green tea leaves for IC50. Evaluation of gel mask preparations include, organoleptic examination and homogeneity, pH, viscosity, dry time of preparation and testing of antioxidant stability. F2 provides better and higher free radical reduction activity than products on the market. F4, F5, F6 shows an increase in free radical reduction activity. Keywords: Green tea leaves (Camellia sinensis L.), DPPh, IC50 gel mask.